Taxation of company reorganisations - Miller, Pete (Tottel Pub., 2009)
This practical day-to-day guide to the tax provisions of commercial reorganisations and reconstructions enables tax practitioners working in this increasingly important area of UK taxation to accurately negotiate their clients' commercial reorganisation transactions. This new edition is fully revised and updated and covers new legislation relating to the latest implementation of EU Directives into UK tax law. The authors provide clear analysis of all relevant legislation, including the technical and practical consequences of commercial transactions, along with information on transactions of all sizes, from major corporate groups to owner-managed businesses. An essential reference source for tax advisers who need to offer clear guidance to client companies that are reorganising, amalgamating or demerging.